Regional Agreement on Access to Information, Public Participation and Justice in Environmental Matters in Latin America and the Caribbean - NU. CEPAL (ECLAC, 2018)
The Regional Agreement on Access to Information, Public Participation and Justice in Environmental Matters in Latin America and the Caribbean was adopted at Escazú, Costa Rica, on 4 March 2018. Opening for signature at United Nations Headquarters in New York on 27 September 2018.